Application of Ice Breaker to Improve Student Learning Outcomes in Elementary School PKN Lessons: Penerapan Ice Breaker Untuk Meningkatkan Hasil Belajar Siswa Pelajaran PKN Sekolah Dasar - Wati, Yuyun Indah; Udin, Bahak (Indonesian Journal of Education Methods Development, 2021)
The purpose of this study was to determine the effect of Ice Breaking to improve student learning outcomes in Civics lessons for second graders of SD Quality Krembung. This researcher uses quantitative research with experimental methods and uses a form of pre-experimental design type One-Shot Case Study. The population used as the object of research is the second grade students of SD Quality Krembung. The sampling technique used in this study is a saturated sampling technique. The sample used in this study were all second grade students of SD Quality Krembung, totaling 28 students. The instrument used in this research is posttest. From the results of the study, the lowest student posttest score was 64 and the highest student score was 96 so that their average score was 82.07. It can be concluded that Ice Breaking has an effect on student learning outcomes in Civics lessons for second grade students of SD Quality Krembung.